The effect of orthostatic hypotension on cerebral blood flow and middle cerebral artery velocity in autonomic failure, with observations on the action of ephedrine. Issue 8 (August 1989) - Brooks, D J; Redmond, S; Mathias, C J; Bannister, R; Symon, L
Abstract : Cerebral blood flow (CBF) and middle cerebral artery velocity (MCAv) have been measured using 133xenon washout and transcranial Doppler in ten patients with autonomic failure. Four pure autonomic failure and four multiple system atrophy patients behaved similarly: tilting them sufficiently to induce significant orthostatic hypotension without causing syncopal symptoms led to a significant fall in their mean MCAv, but no change in their mean CBF. These findings suggest that cerebral autoregulation is preserved in autonomic failure, orthostatic hypotension resulting in a reactive vasodilatation which lowers MCAv, reduces vascular resistance, and maintains CBF. Ephedrine helped to correct the orthostatic hypotension, but had no direct effect on CBF. Two siblings with orthostatic hypotension secondary to dopamine-beta-hydroxylase deficiency also had preserved cerebral autoregulation, but ephedrine led to paradoxical hypotension in these patients.